2009
DOI: 10.1016/j.chom.2009.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Protects C. elegans from Lethal Effects of Enteropathogenic E. coli by Activating Genes that Regulate Lifespan and Innate Immunity

Abstract: SUMMARY Caenorhabditis elegans exhibit avoidance behavior when presented with diverse bacterial pathogens. We hypothesized that exposure to pathogens might not only cause worms to move away but also simultaneously activate pathways that promote resistance to the pathogen. We show that brief exposure to the virulent or avirulent strains of the bacterial pathogen enteropathogenic E. coli (EPEC) “conditions” or “immunizes” C. elegans to survive a subsequent exposure that would otherwise prove lethal. Conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 56 publications
5
88
1
Order By: Relevance
“…For example, the global virulence regulator Ler is essential for virulence of rabbit enteropathogenic E. coli (REPEC) and www.perspectivesinmedicine.org C. rodentium in the weaned rabbit and mouse models of infection, respectively Zhu et al 2006), and is similarly required for colonization of C. elegans by EPEC (Mellies et al 2006). In addition, EPEC is shown to elicit a protective response in C. elegans through induction of genes regulating nematode innate immunity in response to pathogen exposure (Anyanful et al 2009). C. elegans provides a straightforward in vivo system in which to study EPEC attachment and colonization factors (Mellies et al 2006), however, practical limitations to this model do exist as C. elegans cannot survive at the optimal temperature required for expression of the virulence machinery of A/E pathogens (Umanski et al 2002).…”
Section: In Vivo Infection Modelsmentioning
confidence: 99%
“…For example, the global virulence regulator Ler is essential for virulence of rabbit enteropathogenic E. coli (REPEC) and www.perspectivesinmedicine.org C. rodentium in the weaned rabbit and mouse models of infection, respectively Zhu et al 2006), and is similarly required for colonization of C. elegans by EPEC (Mellies et al 2006). In addition, EPEC is shown to elicit a protective response in C. elegans through induction of genes regulating nematode innate immunity in response to pathogen exposure (Anyanful et al 2009). C. elegans provides a straightforward in vivo system in which to study EPEC attachment and colonization factors (Mellies et al 2006), however, practical limitations to this model do exist as C. elegans cannot survive at the optimal temperature required for expression of the virulence machinery of A/E pathogens (Umanski et al 2002).…”
Section: In Vivo Infection Modelsmentioning
confidence: 99%
“…Interestingly, it is known that noxious exposure with bacterial pathogens changes C. elegans food preferences (47). In addition to this simple behavior, Anyanful and colleagues (3) showed that preexposure to some pathogenic bacteria can enhance protective responses of C. elegans to a subsequent infection of the pathogen via dopaminergic neurons that activate conserved signaling pathways, a phenomenon they refer to as "conditioning." However, the challenges with nonpathogenic or health-promoting bacteria and their molecular pathways involved in this phenomenon are poorly understood.…”
mentioning
confidence: 99%
“…The death of the nematode, as a consequence of colonization, typically occurs over several days and is referred to as "slow killing" (75). In contrast, contact-independent killing is mediated through structurally and functionally unrelated exotoxins that are secreted by diverse pathogens, including EPEC (2,3), Pseudomonas aeruginosa (32,57), and Burkholderia cenocepacia (51), among others, that lead to toxicity in the nematode (75). Intoxication of the worms is a relatively rapid pathophysiological process occurring over a period of hours and is referred to as "fast killing" (75).…”
mentioning
confidence: 99%
“…Moreover, none of the virulence determinants previously implicated in mammalian pathogenesis were necessary for nematocidal activity (59). In contrast, on nutritionally rich medium (LuriaBertani [LB] or E. coli direct agar [ECD]) supplemented with tryptophan, EPEC synthesizes diffusible exotoxins that lead to rapid paralysis and subsequent death of the nematode within a few hours (2,3). Exotoxin-induced lethality requires the bacterial enzyme tryptophanase.…”
mentioning
confidence: 99%